Impact of Power Supply Wheeled Vehicles of Public Transport on Pollution Emission - Maciej GLINIAK; Janusz TABOR; Tomasz BYLICA (Communications of International Proceedings, 2021)
The aim of the work was to analyze the emission of pollutants produced by the MPK Kraków fleet stock during the year, and to compare it with several exemplary variants. The first of them was a summary of the emissions of the current MPK Krakow rolling stock, consisting mostly of diesel-powered buses, with a fully complex fleet of hybrid buses, two Solaris Urbino 12 hybrid and Solaris Urbino 18 hybrid models were adopted for the analysis. In the next variant, the current MPK Kraków rolling stock was compared with the rolling stock fully composed of electric buses, the adopted models were Solaris Urbino 12E and Solaris Urbino 18 E, and the rolling stock consisting of hybrid buses and the rolling stock consisting of electric buses were compared. Finally, the costs of changing the existing buses of the MPK Kraków rolling stock to electric buses were calculated, so that the entire rolling stock could consist of low-emission electric buses.
Keywords: Fleet; emission; hybrid; electric; standard